El vino en el mundo urbano riojano a finales de la Edad Media - Goicolea Julián, Francisco Javier (En la España Medieval, 2007)
Wine production and commerce in the Rioja (Haro, Arnedo, Laguardia, Logroño, Herce, Calahorra, Briones and other localities). The ownership of vineyards and wine cellars. The organization of local markets and sale in exterior markets. Wine consumption in the daily diet.